DESKRIPSI PENYEBAB KEMATIAN PADA KORBAN KECELAKAAN SEPEDA MOTOR YANG DIOTOPSI DI INSTALASI KEDOKTERAN FORENSIK RSUP DR. SARDJITO YOGYAKARTA TAHUN 2011-2012 - , RATNANGGANA SISTAPARAMITHA LUK; , dr. Wikan Basworo, Sp.F ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Road traffic accident (RTA) in the Special Province of Yogyakarta are mostly involving motorcycles and the accident cases are increasing every year so it is very important to do research on the number of events and the proportion of deaths from motorcycle RTA to provide an overview of epidemiology. Objective: To understand the proportion of event and death and the prediction of cause of death based on the location of lesion of the motorcycle accident victims autopsied in Forensic Unit of Dr. Sardjito Central Hospital in Yogyakarta. Method: The research is a descriptive observational research using the body victim data of motorcycle traffic accident autopsied in the Forensic Unit of Dr. Sardjito Central Hospital during the year 2011 and 2012 as the subject. It is conducted during December 2013 in Forensic Unit of Dr. Sardjito Central Hospital using the medical record data. Data are stratified to several groups: sex, age, occupation, road user category, victim management, type of accident, and data of lesion. Analysis of lesion is conducted to predict cause of death. Data are presented in table and pie chart. Result: Based on the result it is obtained: (1) Death victims are mostly male at 73.9%. Age range 16-25 years old are the highest range at 42.04%. Private emlpoyee is highest at 62.5%. (2) The number of death is 86.36% driver. Management of death victims is 100% managed through external examination and none is through internal examination. As much as 78.41% are due to colling crash with second party. (3) Location of injury is predicted to be the cause of death is mostly in head trauma at 84.09%. Femur fractures are 2.27% and mixture is 13.64%. Conclusion: More than 80% of the predicted location of the injury to be the cause of death was found in the head and neck.